Myasthenia gravis complicated by pure red cell aplasia with clonal large granular lymphocytosis in the absence of thymoma: a rare case report and literature review - Du, Lijun; Liu, Yiping; Zhou, Qiaolin; Xu, Fang (Frontiers in Immunology, 2025)
In 2013, a young woman during her early pregnancy was repeatedly hospitalized due to respiratory and swallowing difficulties. The pregnancy was terminated due to recurrent severe lung infections. She was later diagnosed with myasthenia gravis (MG) based on positive acetylcholine receptor antibodies. Her muscle weakness was subsequently well-controlled with pyridostigmine bromide, azathioprine, and prednisone. Notably, in the seventh year after her MG diagnosis (2021), the patient developed severe anemia (hemoglobin: 44 g/L). Bone marrow analysis revealed a rare combination of pure red cell aplasia (PRCA) with clonal expansion of large granular cells. Further examinations excluded thymoma. Considering the possibility of drug-induced PRCA, azathioprine was replaced with tacrolimus. Remarkably, the anemia resolved within 1 month, and her MG remained well-controlled. It is well-established that abnormal thymic hyperplasia within thymomas can alter the distribution and function of peripheral T lymphocytes, leading to the development of autoimmune diseases such as MG and PRCA. In this unique case without thymoma, we discussed the mechanisms and associations of PRCA with MG, medication, and clonal large granular T cells. This unique case highlights the unprecedented association of MG and PRCA without thymoma, underscoring the complexity of the disease spectrum. The patient’s subsequent successful delivery in June 2023 adds another dimension to the multifaceted clinical course, warranting attention and exploration into potential connections between these conditions.